An Analytical Psychological Examination of Delayed Marriage Among Islamic Boarding School Students in Salatiga City - Diah Nuraini; Nur Mifchan Solichin (Kopertais Wilayah X Jawa Tengah, 2025)
This study examines the phenomenon of marriage delay among Islamic Boarding Scholl Students (Santri) in Salatiga City through the perspectives of Islamic law and Carl Gustav Jung’s Analytical Psychology. This research is significant because it highlights the increasing tendency of Santri, a group strongly associated with high religiosity and the belief that marriage is a form of worship to postpone marriage. The phenomenon reflects a tension between traditional Islamic values and modern realities, in which financial readiness, emotional maturity, and personal development have become key considerations before marriage. The research employs a qualitative approach with a case study design. Primary data were collected through semi-structured in-depth interviews with 19 Santri from three Islamic boarding schools in Salatiga. Secondary data were obtained from classical Islamic literature and psychological studies on marriage. Data were analyzed using the interactive model of Miles and Huberman, which involves data reduction, data display, and conclusion drawing. The analytical framework integrates Islamic legal principles are ahkāmu nikāh, istiṭā‘ah, and kafā’ah with Jung’s Analytical Psychology, particularly the concepts of psyche, archetype, and individuation. The findings reveal that Santri postpone marriage due to concerns about financial preparedness, long-term commitment, and shifting social values. From the perspective of Islamic law, such delay is considered permissible as long as it does not violate religious principles. From the perspective of Analytical Psychology, delaying marriage represents a complex psychological process that reflects deep individual consideration between religious consciousness and modern personal aspirations.